Los náufragos del Spitzberg - Salgari, Emilio, 1862-1911.; Jimenez, Antonio. (Madrid : Saturnino Calleja Fernandez)
Electronic reproduction. Mode of access: Internet. Benchmark for Faithful Digital Reproductions of Monographs and Serials. Version 1. December 2002. Digitized.